The Effect of Packaging Defect Types on Consumer Purchase Decisions of Wafer Roll Products by PT XYZ in Surabaya City - Selvina Puspita Sari; Ulya Sarofa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The packaging validation process at PT XYZ in Surabaya City faces obstacles due to packaging defects that cause problems in terms of time and cost efficiency. In addition, these packaging defects also have the potential to influence consumer purchasing decisions. This study aims to determine the influence of packaging defect types on consumer purchasing decisions for wafer roll products at PT XYZ in Surabaya City. This study was conducted using a survey method with a non-probability sampling technique involving 150 respondents. The types of packaging defects studied include cutterseal folding, cutterseal book folding, longseal folding, and longseal misalignment. Data were analyzed using the SPSS application program version 27.0 through multiple linear regression tests to determine the influence of packaging defect types on consumer purchasing decisions. The results showed that the types of packaging defects, namely cutterseal folding, longseal folding, and longseal misalignment, influenced purchasing decisions, while the cutterseal book folding defect type did not influence purchasing decisions. Overall, the coefficient of determination value showed a figure of 20%, indicating that packaging defect types only contributed 20% to consumer purchasing decisions, and the influence was classified as weak. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production